Ablation Depth-Dependent Survival Analysis of Phototherapeutic Keratectomy for Recurrent Corneal Erosion Syndrome - Kunal A. Gadhvi; Georgios Vakros; Alfredo Borgia; Kirithika Muthusamy; Laura de Benito-Llopis; Alexander C. Day; Daniel M. Gore (Ophthalmology and Therapy)
Abstract Introduction Phototherapeutic keratectomy (PTK) is a treatment for recurrent corneal erosion syndrome (RCES). The aim of this study was to investigate whether deeper ablations yielded greater success rates. Methods Retrospective case notes review with prospective patient-reported outcome measures for all patients who had undergone PTK for RCES at a single tertiary referral unit. Patients received treatment with the Schwind Amaris® 750 s excimer laser. The primary outcome measure was recurrence-free survival of patients with ablation depth ≥ 15 µm compared to < 15 µm. Results Seventy eyes of 63 patients were included for analysis, of whom 39 (56%) had preceding trauma and 20 (29%) had epithelial basement membrane dystrophy (EBMD), with the remaining 11 (15%) of unknown aetiology. Twenty eyes (29%) received an ablation ≥ 15 µm (mean ablation depth 16.85 ± 3.4 µm) and 50 (71%) received < 15 µm (mean ablation depth 9.26 ± 1.5 µm). Overall, 65 eyes (93%) reported a subjective improvement in symptoms, with 46 (66%) remaining completely symptom free at the last follow-up [mean follow-up 24 (range, 9–48) months]. Eighty-five per cent of eyes in the ≥ 15 µm group remained symptom free compared to 58% of those with < 15 µm (p = 0.036). Conclusion PTK is an effective treatment for RCES, with deeper ablations yielding longer symptom-free survival.